Diagnosa Penyakit Mata Berdasarkan Citra Ocular Disease Intelligent Recognition (ODIR) Dengan Gabor Filter Klasifikasi Levenberg-Marquardt - Sinaga, Anita Sindar; Ginting, Feby; Ramen, Sethu - (PRPM STMIK TRIGUNA DHARMA, 2023)
Light captured by both eyeballs is passed on to the pupil, focused through the sensitive part of the eyeball. The retinal organ of the eye converts the light capture into nerve impulses, and delivers them to the brain through the nerve fibers contained in the impulses. There are several complications of disease in the sense of sight that can be diagnosed from the arrangement of the retina of the eye. Image segmentation stages are needed so that the fiber contained in the retinal optics can be changed. The initial stage is with the initialization of the arrangement for the contour movement stages. Using the Levenberg-Marquardt algorithm is able to improve the following results obtained as a basis for previously collected data. In this study eye disease only diagnosed eye disease in complaints of the retina of the eye. The purpose of this research is to diagnose early sight diseases that appear based on the symptoms shown by the composition of the retinal parts of the human eyeball and classify the level of danger of the results of eye disease diagnoses.